Farmer training workshops on understanding probabilistic seasonal forecasts: Wote, Kenya, 14-16 and 20-23 September 2011 - Njiru E; Ariithi CKK; Rao, K.P.C.; Mutinda D; Hansen, James (2015)
This report presents the work done during farmer training workshops on probabilistic seasonal forecasting and forecast-based advisories, in Wote, Makueni County, Kenya. This activity took into consideration the fact that farmers in Mahueni County in semi-arid eastern Kenya mainly rely on rainfall for their agricultural production. The rainfall is, however, highly variable in amounts and distribution both seasonally and annually making farming in the region a risky business. The goal of the project was therefore, to train farmers in the identified areas of Makueni to better understand the climate of their location and explore how they can manage the effects of the variability in rainfall in order to improve their farm production. The area was selected due to previous as well as on-going studies implemented by ICRISAT, KALRO and other collaborators. The aim of the training was to empower farmers with knowledge on the use of forecast information and to enable them make better use of this knowledge in their farm planning for improved household food security. The trainings were conducted on the 14-16 and 20-23 September 2011, before the onset of the short rain (October-December) season. It was part of a study that covered twelve villages in Wote Division, Makueni County. Ten farmer participants were selected per village giving a total of 120 farmers. These workshops were sponsored by the Climate Change Agriculture and Food Security (CCAFS) project under the Theme “Adaptation through Managing Climate Risk,” and implemented in collaboration with International Crops Research Institute for the Semi-Arid-Tropics (ICRISAT), Kenya Agricultural and Livestock Research Organization (KALRO), Kenya Meteorological Services (KMS), the Ministry of Agriculture (MoA), and International Research Institute for Climate and Society (IRI).